Virilizing Ovarian Steroid Cell Tumor: A Rare Case - Aishwarya Bettegowda; Nagarathnamma Rangaiah; Nagendra Prasad; Savitha Channa Veeregowda (Journal of Clinical and Diagnostic Research, 2015)
Ovarian steroid cell tumours are fewer than 5 percent of sex-cord stromal tumours and 0.1% of all ovarian tumours. The average age at diagnosis is the mid-20s, but patients can present at virtually any age. We present a case of 38-year-old multipara with history of secondary amenorrhea, clinical signs & symptoms of virilization developed over the past 5 years. With elevated (115ng/dL) serum testosterone level and radiological findings of a left adnexal solid mass; the patient was suspected to have a virilizing tumour of left ovary. Laparoscopic left salpingo-oophorectomy was performed. Histopathology revealed tumour cells in small nests with vacuolated to eosinophilic cytoplasm with nuclear atypia completely replacing the ovarian tissue suggestive of steroid cell tumour (NOS) of ovary. The patient was discharged and advised for follow up with serum testosterone levels after 3 weeks.